The Influence of Digital Economic Growth and Productive Work Force Toward Human Development Index in Indonesia Viewed from a Maqashid Sharia Perspective - Malik, Anas; Novelia, Alika; Moh Mukri; Baharuddin, Sitti Aminah (The Postgraduate of Institut Agama Islam Negeri Metro Lampung, 2024)
Introduction: Community productivity is critical in maintaining quality of life to avoid disasters. The use of digital technology in the economic aspect has also provided opportunities for people far from the market to earn income to meet their living needs. Objective: The research problem is formulated as follows: What is the influence of digital economic growth and productive labor on the Human Development Index in Indonesia in 2018-2022, both partially and simultaneously, and how is this viewed from a maqasid syariah perspective?Method: This research is presented as five-year time series data and analyzed using quantitative descriptive methods and multiple linear regression analysis, using Eviews 10 as an analytical tool. The sampling technique used was purposive sampling, with sample criteria in the form of digital economic growth, productive workforce, and data during the 2018-2022 period. Result: The digital economic growth variable partially has a negative and insignificant effect on the Human Development Index. Meanwhile, the productive labor variable positively and significantly affects the Human Development Index. Simultaneously, the growth of the digital economy and productive workforce has had a positive and significant effect on the Human Development Index in Indonesia in 2018-2022. From a maqasid syariah perspective, digital economic activities are permitted if no arguments prohibit them. Implication: This research provides valuable insights that can influence how we view and approach digital economic growth and productive labor in Indonesia's human development context. By considering these impacts, various parties can optimize their strategies to advance people's quality of life more effectively.